Pengaruh Kualitas Layanan Transportasi Suroboyo Bus Terhadap Peningkatan Kepuasan Masyarakat Kota Surabaya - Whildan Primadhanny; Yusuf Hariyoko; Anggraeny Puspaningtyas (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
The study aims to analyze the impact of Suroboyo Bus transportation services on improving the satisfaction of the people of Surabaya. The type of research used in this research is quantitative with survey methods and cross-sectional design. The research was carried out on the Suroboyo Bus public transportation route Rajawali-Purabaya Terminal. This research uses a questionnaire-type instrument using the Likert scale. The number of samples used in this study was calculated using the Slovin formula and samples were obtained from as many as 400 respondents. The data analysis techniques used in this study are instrumental testing, classical assumption testing, hypothesis testing, and double linear regression testing. Instrumental testing results refer to valid and reliable instruments. The results of classic assumptions also showed normal-distributed data and variables X and Y have a linear relationship. The results of the hypothesis test with the F test obtained a P-value of 0,000, so there is a significant influence on the quality of public transport services Suroboyo Bus in general on the improvement of public satisfaction. The result of the analysis of dual linear regregation can be known that all free variables have a positive value coefficient. The determinant coefficent test results showed a large influence of service quality on public satisfactions is 77.49%.